1987
DOI: 10.3133/pp1444
|View full text |Cite
|
Sign up to set email alerts
|

Deposits of pre-1980 pyroclastic flows and lahars from Mount St. Helens Volcano, Washington

Abstract: Mount St. Helens in southern Washington has been one of the most active and most explosive volcanoes in the Cascade Range since its birth about 40,000 years ago. In this report its history is divided into four eruptive stages, the most recent of which is subdivided into six eruptive periods. Prior to 2,500 years ago the volcano erupted tephra, domes, and pyroclastic flows, but only a few lava flows that were large enough to extend beyond the base of the volcano. Most products of volcanism were dacite or silici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
170
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(173 citation statements)
references
References 20 publications
2
170
1
Order By: Relevance
“…Multiple plug domes in the structures of these volcanoes indicate previous eruptions of viscous siliceous magmas, which were able to degas and crystallize in the upper parts of conduits while slowly ascending toward the ground surface. Open conduit eruptions of the plinian type, although they occurred also (especially frequently on MSH; Mullineaux 1986), were relatively rare in the late histories of these volcanoes (Mullineaux and Crandell 1981;Crandell 1987;Wadge and Isaacs 1988;Roobol and Smith 1998;Druitt and Kokelaar 2002).…”
Section: Volcanic Edifices and Summary Of Past Eruptive Activitiesmentioning
confidence: 99%
“…Multiple plug domes in the structures of these volcanoes indicate previous eruptions of viscous siliceous magmas, which were able to degas and crystallize in the upper parts of conduits while slowly ascending toward the ground surface. Open conduit eruptions of the plinian type, although they occurred also (especially frequently on MSH; Mullineaux 1986), were relatively rare in the late histories of these volcanoes (Mullineaux and Crandell 1981;Crandell 1987;Wadge and Isaacs 1988;Roobol and Smith 1998;Druitt and Kokelaar 2002).…”
Section: Volcanic Edifices and Summary Of Past Eruptive Activitiesmentioning
confidence: 99%
“…Crandell established the general eruptive history of Mount St. Helens in the 1960s-1980s through their extensive studies of the tephra deposits found around the volcano. They recognized that the eruptive history was episodic, grouped the tephras into "sets" of similar age and composition (Mullineuax, 1996, and references therein) that they described as a series of eruptive stages and periods, and correlated some of the lava flows, domes, and fragmental deposits (Crandell, 1987). Radiocarbon dating provided some geochronologic control, but Crandell and Mullineaux's work was hindered by the lack of preserved tephras older than ~60 ka, because these had been removed by glaciation.…”
Section: Brief Eruptive History Of Mount St Helensmentioning
confidence: 99%
“…The authors here propose that there simply is no pressurized drainage system conveying water along the bed of the east glacier.The crater glacier grew atop several tens of meters of rubble (mainly rock-avalanche debris) that accumulated on the crater floor following the cataclysmic 1980 eruption [Mills, 1992] .The volcanic edifice beneath this rubble is geo logically complex, consisting of multiple lava flows, pyroclastic and lahar deposits, and other fragmental deposits [Crandell, 1987] .Thus, wa ter that reaches the glacier bed probably flows out of the crater through the thick rubble layer or downward into the volcano's ground-water system, rather than moving along the glacier bed. In support of this hypothesis, it should be noted that there are no outlet streams at the glacier termini, although there are springs and seeps farther downslope.…”
Section: About Glacier and Volcano Hydrologymentioning
confidence: 99%